2006
DOI: 10.1016/j.bpc.2006.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The “interceptor” properties of chlorophyllin measured within the three-component system: Intercalator–DNA–chlorophyllin

Abstract: In aqueous solutions, in the presence of double-stranded DNA, chlorophyllin (CHL) forms complexes with each of the three DNA intercalators: acridine orange (AO), quinacrine mustard (QM), and doxorubicin (DOX). The evidence for these interactions was obtained by measurement changes in the absorption and fluorescence spectra of the mixtures containing DNA and intercalators during titration with CHL. A model of simple competition between DNA and CHL for the intercalator was used to define the measured interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
(53 reference statements)
2
26
1
Order By: Relevance
“…ICR-191 is an aromatic mutagen having a three-ring structure, it intercalates into DNA and has also mustard-like alkylating properties [30,31]. We expected, therefore, that similar as in the case of intercalators studied by us before [23] CHL will also have the interceptor activity towards ICR-191.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…ICR-191 is an aromatic mutagen having a three-ring structure, it intercalates into DNA and has also mustard-like alkylating properties [30,31]. We expected, therefore, that similar as in the case of intercalators studied by us before [23] CHL will also have the interceptor activity towards ICR-191.…”
Section: Introductionmentioning
confidence: 71%
“…We have shown for example, that CHL forms complexes with acridine orange, quinacrine mustard and the antitumor drug doxorubicin, with association constants (K a 's) 7.0 × 10 5 , 3.2 × 10 5 and 3.3 × 10 5 M −1 , respectively [22]. Applying experimental analysis to the three-component interactive system: intercalator-DNA-CHL we observed that CHL attenuated binding of these intercalators to DNA thereby showing the interceptor activity [23]. In the present study using similar experimental approach we investigated interactions between the acridine mutagen ICR-191 and DNA in the absence and presence of CHL.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations